The Effect Of Using Audio Visual Media Based Online On Students' Concept Understanding In Science Courses Quasi Experimental Research Class IV SDN 2 Cigadog - widy nugraha; Neni Nadiroti Muslihah; Dea Asri Pujiasti; ejen jenal mutaqin; Putri Camelia Intansari (Institut Pendidikan Indonesia, 2021)
The essence of science learning is as a product of knowledge in the form of factual, conceptual, procedural and metacognitive knowledge. In this connection, in learning interesting learning patterns must also be applied not only through conventional media. Online-based audio visual media can be used as an alternative when the tools and materials needed are not available. This research is a one-group pretest-posttest design. The population of this research is the fourth grade students of SD Negeri 2 Cigadog. The sample used was randomly selected, namely class V and IV as the experimental class and replication. The data collection technique used was a multiple choice test. Based on the results of hypothesis testing that has been done, it is known that the application of virtual practicum has an effect on students' conceptual understanding. It can be seen from the acquisition that the research class has a value of -17.335> -1.7341, so H0 is rejected and H1 is accepted. This means that there is an effect of online-based audio-visual media on science learning outcomes of fourth grade students at SDNegeri 2 Cigadog.